Holocene changes in the position of the Southern Hemisphere Westerlies recorded by long-distance transport of pollen to the Kerguelen Islands - Zwier, Maaike; van der Bilt, Willem G.M.; Schneider, Tobias; D'Andrea, William J.; Bakke, Jostein; Van der Putten, Nathalie; Bjune, Anne E. (Quaternary science reviews, 2024)
The Southern Hemisphere Westerlies (SHW) are a vital part of the Southern Hemisphere's coupled ocean-atmosphere system and play an important role in the global climate system. The SHW affect the upwelling of carbon-rich deep water and exchange of CO2 from the ocean to the atmosphere by driving the Antarctic Circumpolar Current. On seasonal to millennial timescales, changes in the strength and position of the SHW are associated with temperature and precipitation changes throughout the extratropical Southern Hemisphere. Understanding the behaviour of the SHW under different background climate states is important for anticipating its future behaviour and remains a subject of ongoing research. Terrestrial paleoclimate records from lake sediments are valuable for reconstructing past atmospheric change and records from the handful of sub-Antarctic islands provide the opportunity to develop datasets to document spatio-temporal patterns of long-term SHW behaviour. Here, we generate palynological, microcharcoal, and sedimentological reconstructions (including CT imagery, μXRF analysis, magnetic susceptibility, and loss-on-ignition) on lake sediments from the Kerguelen Islands (49°S) to constrain variability in Holocene vegetation, climate, and atmospheric circulation (SHW position). Due to the influence of the SHW on the Kerguelen Islands, the influx of long-distance transported (LDT) pollen and microcharcoal from southern Africa serve as proxies for the meridional position of the SHW. In contrast with the stable conditions that prevailed on the Kerguelen Islands over the past 8,600 cal yr BP, our findings reveal a highly dynamic Early Holocene period. Consistent with local palynological evidence of warmer conditions, a high influx of LDT pollen and charcoal from southern Africa suggest that the SHW core belt was located further south of the Kerguelen Islands during this time. Comparison against paleoclimate records from the surrounding region and beyond suggests that the inferred changes might be explained by changes to our planet's interhemispheric thermal gradient, triggered by North Atlantic cooling in response to melting of the last remnants of the Laurentide Ice Sheet. •We study Holocene vegetation and atmospheric circulation on the Kerguelen Islands.•Southern Hemisphere Westerlies position is based on long-distance pollen transport.•Wind belt shifts coincide with changes in local temperature and precipitation.•Durin the Early Holocene the core wind belt was positioned south of the Kerguelen.•From 8,600 cal yr BP the core wind belt shifted northward of the Kerguelen Islands.